INVESTIGATION ON THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT OF UNIVERSITY STUDENTS - O. V. Kotomina (Образование и наука)
. Introduction. In recent decades, emotional component during the education process has been widely studied by Russian and foreign researchers. The problems of emotional intelligence formation at the higher school have received much attention due to the fact that development of this psychological characteristic of a personality positively influences students’ motivation to training, adaptation at university and academic results of education. Students with high level of emotional stability, able to adequately perceive own and other experiences, and to control them, can master professional competences more successfully; as a matter of practice, those students become good communicators. Thus, such graduates become high-demand specialists in labour market.The aim of this article is to present the results of the research conducted by the author in order to identify the interrelation between emotional intelligence of future managers and their academic achievement.Methodology and research methods. Analytical review of scientific literature was undertaken at the initial stage of work; that allowed to receive general perception of a state of knowledge of the studied problem and to define methods. D.V. Lyusin questionnaire (psychodiagnostic technique based on the self-report and complemented in connection with specifics of the respondent base) was used to study various aspects of the students’ emotional intelligence. The online form of the survey was developed for the convenience of interaction with students and rapid data collection; the results were processed by means of correlation analysis.Results and scientific novelty. The results of the survey showed the average level of development of emotional intelligence among Management students. Interpersonal component of emotional intelligence has proven to be the most pronounced. The correlation analysis of the data revealed a statistically significant interrelation between the level of emotional intelligence and academic achievement of students. However, contrary to the hypothesis, that interrelation turned out to be negative. With reference to the established facts, it has been suggested that students with the high level of emotional intelligence treat their academic grades more calmly, building full-fledged balance between studies, work and private life.Practical significance. The present findings of the research and results of the first stage of a longitudinal panel investigation of opportunities of psychology and pedagogical influence on development of university students’ emotional intelligence can be used by academic teaching staff of higher education institutions for further work with students.